Collusion in Beauty Contests - Achim Wambach (Center for Economic Studies and ifo Institute (CESifo), 2002)
During the recent sales of UMTS licenses in Europe some countries used auctions while others resorted to so-called Beauty Contests. There seems to be a wide consensus among economists that in these and other contexts like privatisation an auction is the better selling mechanism. However, why exactly an auction should be preferred is unclear. Here we present an argument why beauty contests or negotiations might be dominated by auctions, which is closely linked to the multi dimensionality on issues involved in this process. The important assumption we make is that bidding firms do not know the preferences of the government. As a consequence, during a beauty contest participants are uncertain about the final decision of the government. This uncertainty enables firms to collude.
Keywords: 330; auctions; collusion; beauty contests.